EFFECT OF COMBINATION SODIUM ALGINATE-GELATIN 1% : 2% CONTENT IN CHARACTERISTIC AND ANTIMICROBIAL ACTIVITY OF PROBIOTIC MICROSPHERES Lactobacillus acidophilus - Regia Nada Asshafa; Tutiek Purwanti; Dewi Melani Hariyadi (UPT Penerbitan Universitas Jember)
Probiotics is live micro-organisms which whenadministered in adequate amounts, confer ahealth benefit on the host (FAO / WHO, 2002).Probiotics may give therapeutic effect in minimalamounts 106-107cfu/g daily. Some reports in thelast decade have described that probiotic, such asLactobacillus acidophilus, is useful for treating skindisorder such as dermatitis, acne, cellulitis, andpsoriasis. This relates to the content of probioticsmetabolites that protect the skin from mostpathogenic bacteria, such as Staphylococcusaureus, and improve skin structure (Cinque et al.,2011).In topical application, the active ingredient shouldlast a long time on the skin and prolonged release.Meanwhile, Lactobacillus acidophilus unstable toenvirontment factors, such as the hightemperature, oxygen, and humidity (Al-Hurr,2011). Therefore, probiotics encapsulation isneeded. In addition, encapsulation also mayprovide prolonged release so that its effectivenessincreased as antimicrobial activity becomes longer.Encapsulation process that forms microparticles (1-1000 μm) called micro-encapsulation. Sphericalmicroparticles called microspheres (Sahil et al.,2011). The recommended size of microsphereswhich active ingredient site action is in epidermislayer is 5-300 μm (Chadawar and Shaji, 2007).Sodium alginate is widely used as a matrix ofmicroencapsulated probiotics. Microspheres madewith sodium alginate matrix may improve theviability of probiotics during storage. Gelatin alsooften used in microencapsulated probiotics(Solanki et al., 2013). Gelatin is biodegradable,non-toxic, and easy to experience a cross-linking sothat it can be used in the preparation of colloidaldelivery systems, such as microspheres andnanoparticles (Sailaja, et al., 2010).Type of matrix influence the characteristic ofmicrosphere. Microspheres are only made withsodium alginate tend to provide simultaneousrelease. Therefore for prolonged release, sodiumalginate should be combined with gelatin (Lee etal., 2014; Roy et al., 2009). Combination of sodiumalginate and gelatine in the ratio 1: 2 will providesmall particle size that not easily aggregate duringthe process of mixing and drying (Lee et al., 2014).In this study, microspheres were formed by crosslinking between combination of sodium alginateand gelatin (1% : 2%) with CaCl2 as cross linkerusing ionotropic gelation method.OBJECTIVEThe aim of this research was to investigaste theeffect of combination of sodium alginate andgelatin (1% : 2%) content in characteristics andantimicrobial activity of probiotic microspheresLactobacillus acidophilus.